Studi In Silico Theaflavin sebagai Agen Anti-Photoaging: Studi In Silico Theaflavin sebagai Agen Anti-Photoaging - Febyani, Putu Dewi; I Gede Bayu Krisnayana (Jurnal Jejaring Matematika dan Sains, 2022)
Photoaging is skin aging due to extrinsic factors. Photoaging occurs due to excessive degradation of collagen caused by excessive exposure to UV radiation. Excessive UV exposure triggers induction of MMP-1 activities that actively degrade collagen in skin. Theaflavin is known to have pharmacological activity related to anti-photoaging. This study aims to determine the mechanism of MMP-1 inhibition by theaflavin, a polyphenol compound with high antioxidant activity, using in silico molecular docking. Molecular docking in silico is carried out in several step such as optimization of the 3D structure of theaflavin compounds, preparation of target protein, method validation, and docking between optimized theaflavin compounds and the MMP-1 enzyme (PDB ID: 966C) which refers to the binding energy parameter where The lower the binding energy value, the stronger and more stable the bond between theaflavin compound and the MMP-1 enzyme will be. The results obtained in the form of an binding energy between theaflavin compound with the MMP-1 enzyme, which is -10,56 kcal/mol, while the binding energy native ligand with the MMP-1 enzyme is -11,03 kcal/mol. This energy indicates that theaflavin compounds have potential as anti-photoaging agents because they are able to inhibit the MMP-1 enzyme.